(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The linguistics of modern Uzbekistan is characterized by an in-depth study of foreign languages, both in theoretical and practical aspects, as well as the development of new directions aimed at studying the language in terms of studying the processes of thinking, the place and role of man in an increasingly complex world, the specifics of a person’s speech behavior within different social groups (language pragmatics).